INFORMATION SYSTEM FOR DRUG MANAGEMENT OF PULMONARY TUBERCULOSIS PATIENT - Iwan Stia Budi; Yustini Ardillah; Amrina Rosyada (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Android and web-based application for monitoring patients with tuberculosis for puskesmas level programMulti-drug resistant tuberculosis (MDR TB) is a challenge in every country with a high prevalence of TB, including Indonesia. MDR TB itself is influenced by many factors including the lack of discipline in taking medication due to forgetfulness or rejection from the patient. This study aims to design a prototype of the drug-taking companion management information system (PMO) of pulmonary tuberculosis patients. The stages of this design are system requirements analysis, logical design, physical design, and interface. The results of the prototype design will be tested with officers responsible for TB and supervisors taking medication. This android platform-based application helps supervisors to remind patients to take their medicine regularly and the dose. This application continues to be developed by fixing bugs and creating a channel for user complaints